A case study on the perception of selected Philippine librarians on the evolution of the library profession - Laxamana, Mary Allyson Claude C. (School of Library and Information Studies, University of the Philippines Diliman, 2017)
Librarians are required to learn what their users need in order for them to give the best services. Since technologies and the internet are continuously on the rise, it makes librarians change how they provide the information that is asked of them by learning how to integrate them with their library. Instead of making librarians obsolete, let them evolve into something better for the library by combining these concepts in making them possible for the library and introducing the new geek librarian. The geek librarian is defined as a librarian who is a digital technology expert or enthusiast and applies his skills and knowledge into the development and improvement of the library.